Performance Audit of Indian System of Medicines and Homeopathy in Madhya Pradesh - CAG of India (CAG of India, 2005)
The Directorate of Indian System of Medicines and Homoeopathy in Madhya Pradesh was established to implement various programmes and schemes of delivery of health services, imparting education, production of medicines etc. in the systems of Ayurveda, Homoeopathy & Unani with the assistance of District Ayurveda Officers, Principals of colleges and Superintendents of pharmacies in the State. It functioned under the Medical Education Department of Madhya Pradesh Government. There was an audit observation with regard to the Directorate of Indian System of Medicines and Homeopathy in Madhya Pradesh in Audit Paragraph 3.20 of the Report of the Comptroller and Auditor General of India on Madhya Pradesh for the year ended 31 March 1998. This performance audit covers the period 1999-2000 to 2003-04 and it was conducted through examination of records at the Directorate of Indian System of Medicines and Homeopathy, District Ayurveda Officers in 11 districts out of 45, two pharmacies (Bhopal and Gwalior) and four colleges out of nine (Ayurveda - Bhopal and Gwalior, Unani and Homeopathy - Bhopal). Main audit objectives of this performance audit were to assess: 1. Whether health care services under State programmes and Centrally Sponsored Schemes pertaining to ISM&H were properly delivered in rural and urban areas, 2. Adequacy and utilisation of facilities and infrastructure for education and training in these systems of medicines, 3. The economy and the efficiency in production and procurement of medicines and 4. The monitoring and evaluation mechanism, for administering the ISM&H activities in the State.
For the Period 1999-2000 to 2003-04